(untitled) (Biological Sciences - PJSIR, 2006)
Tannery industry in Pakistan occupies an important place in the national economy. The magnitude of chrome effluent waste generated by the industry has rapidly multiplied during the past decade. This has caused an irreversible damage to the ‘flora and fauna’, which demands immediate remedial action. An effort has been made to develop indigenous means to combat chromium pollution with humic acids. Humic acids (HA) are polymeric, brown complex of compounds occurring in the aquatic, terrestrial and sedimentary environments. Soft brown coals and leonardite are major sources of humic acids, which contain up to 80% extractable humic acids. These economical, coal-derived humic acids are useful for soil and water remediation. The process reported in the present study for this purpose is simple, economical and avoids the problems associated with the disposal of bulky chromium waste produced using coagulation and other techniques.